Kualitas Akrual Memoderasi Earnings Opacity Terhadap Biaya Ekuitas - Liza Andriani; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to examine the effect of earnings opacity on the cost of equity with accrual quality as a moderating variable. This studyuses two measures for earnings opacity which are earnings aggressiveness and earnings smoothing. Number of sampleis 40 manufacturing companies that distribute dividend periods 2015-2017. The method of analysis using interaction moderation regression.The results of this study showed that accrual quality strengthen the relationship between earnings aggressiveness and cost of equity. Accrual quality also weaken the relationship between earnings smoothing and cost of equity. Earnings aggressiveness has positive and significant effect on cost of equity. Earnings smoothing has positive but not significant effect on cost of equity.